2018
DOI: 10.1111/apa.14344
|View full text |Cite
|
Sign up to set email alerts
|

Observation study showed that the continuity of skin‐to‐skin contact with low‐birthweight infants in Uganda was suboptimal

Abstract: AimKangaroo mother care (KMC) is a safe and effective method of reducing neonatal mortality in resource‐limited settings, but there has been a lack of data on the duration of skin‐to‐skin contact (SSC) in busy, low‐resource newborn units. Previous studies of intermittent KMC suggest the duration of SSC ranged from 10 minutes to 17 hours per day.MethodsThis was an observational study of newborn infants born weighing less than 2000 g, which collected quantitative data on SSC over the first week after birth. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
2
20
1
2
Order By: Relevance
“…Our results indicate that even smaller doses during the first days of life may be highly beneficial. Our study does not allow us to directly understand the KMC mechanism, but the main links highlighted in the literature (12)(13)(14)(15)(16)(17) such as bonding, breastfeeding, stimulation, are likely to apply in this setting as well. Further research will be needed to confirm the results of this study, and to identify optimal and minimal dosing of KMC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results indicate that even smaller doses during the first days of life may be highly beneficial. Our study does not allow us to directly understand the KMC mechanism, but the main links highlighted in the literature (12)(13)(14)(15)(16)(17) such as bonding, breastfeeding, stimulation, are likely to apply in this setting as well. Further research will be needed to confirm the results of this study, and to identify optimal and minimal dosing of KMC.…”
Section: Discussionmentioning
confidence: 99%
“…Skin-to-skin contact has been shown to increase attachment, enhance mothers' ability to breastfeed, and stimulate the child (12,13). Several recent studies have underscored the effectiveness and cost-effectiveness of KMC in particular for reducing infant mortality among preterm and low birth weight children, but also for reducing the likelihood of severe illness and infections, and for reducing average length of stay at the hospital (14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Among five RCTs that promoted continuous KMC, three reported durations of ≥ 20 h/day [18,57,58] and two did not report duration [15,59]. Among 16 RCTs evaluating intermittent KMC in stable neonates, one reported mean/median duration of 17 h/day, five reported 10-14 h/day and nine reported < 10 h/day [60]. The OMWaNA trial will employ a comprehensive approach to improve adherence.…”
Section: Challenge 1: Timely Recruitment With Informed Consentmentioning
confidence: 99%
“…Our study found high daily duration of skin-to-skin practice overall, with over 84% of women reporting at least 10 hours or more in facility. A mapping of related RCTs in the 2016 Cochrane Review of KMC identified 16 studies that reported on the mean daily duration of skin-to-skin contact and found that the mean daily hours of KMC ranged from 10 minutes to 17 hours per day [3,18]. Among these studies, Watkins et al found none from sub-Saharan Africa, and the method of recording hours of skin-to-skin was rarely reported as observation, self-report, or other methods [18].…”
Section: What We Recommend?mentioning
confidence: 99%
“…Currently, there are limited data from low-resource settings on the duration of skin-to-skin practice [18] and on KMC practice with different types of wraps [19]. We conducted this study to address the evidence gap on the acceptability and effectiveness of a custom KMC wrap on adherence to skin-to-skin practices in Malawi.…”
Section: Introductionmentioning
confidence: 99%